Moral History from Herodotus to Diodorus Siculus - Hau, Lisa Irene (Edinburgh University Press, 2016)
Why did human beings first begin to write history? Lisa Irene Hau argues that a driving force among Greek historians was the desire to use the past to teach lessons about the present and for the future. She uncovers the moral messages of the ancient Greek writers of history and the techniques they used to bring them across. Hau also shows how moral didacticism was an integral part of the writing of history from its inception in the 5th century BC, how it developed over the next 500 years in parallel with the development of historiography as a genre and how the moral messages on display remained surprisingly stable across this period. For the ancient Greek historiographers, moral didacticism was a way of making sense of the past and making it relevant to the present; but this does not mean that they falsified events: truth and morality were compatible and synergistic ends.